Identification of Raoultella terrigena as a Rare Causative Agent of Subungual Abscess Based on 16S rRNA and Housekeeping Gene Sequencing - Yu Wang; Xiawei Jiang; Zemin Xu; Chaoqun Ying; Wei Yu; Yonghong Xiao (Canadian Journal of Infectious Diseases and Medical Microbiology)
A 63-year-old-man was admitted to our hospital with severe subungual abscess. Bacteria were isolated from pus samples, and an inconsistent identification was shown by VITEK 2 system and MALDI-TOF mass spectrometry as Raoultella planticola and Raoultella terrigena, respectively. Molecular identification by 16S rRNA sequencing suggested that the isolate is R. terrigena, and this was further demonstrated by sequencing three housekeeping genes (rpoB, gyrA, and parC) with phylogenetic analysis. To our knowledge, this is the first report of subungual abscess caused by R. terrigena, a rare case of human infection due to soil bacterium. Our study highlights the technique importance on this pathogen identification.